Which passengers are on your bus? A taxonomy of the barriers adolescents with chronic pain face in achieving functional recovery. (8th November 2020) - Jacobs, Konrad; Smith, Alisha; Heathcote, Lauren C.; Caes, Line
Abstract: Background: Despite evidence that intensive interdisciplinary pain treatment (IIPT) is effective in facilitating functional recovery in adolescents with chronic pain, engagement with IIPT is suboptimal among adolescents. A key aspect of IIPT is to support functional recovery via (re)engagement with age‐appropriate daily activities. The aim of this study was to gain a comprehensive insight into adolescents' perceptions of the barriers they need to overcome to engage with age‐appropriate activities in order to achieve functional recovery. Methods: Forty‐one adolescents who were starting an IIPT programme completed the 'passenger‐on‐the‐bus metaphor', an exercise in which they identify and describe their perceived barriers (i.e. 'passengers' on their bus) that prevent them from engaging with age‐appropriate activities. The responses were analysed using inductive thematic analyses to generate a taxonomy of perceived barriers to functional recovery. Results: We generated a taxonomy of seven different barriers that participants described facing on their road to functional recovery: physical constraints, being 'fed up', low self‐confidence and self‐esteem, perfectionism, avoidance of engagement with pain, feelings (such as sadness, anger, guilt, anxiety) and social barriers (received from a range of sources such as parents, friends, school and wider society). Conclusion: The findings reveal a variety of barriers that were perceived to hinder functional recovery through reduced engagement with age‐appropriate activities and thereby hamper progress within IIPT. The Passenger on the bus metaphor can be used to identify similar barriers faced by adolescents in an individualized treatment approach, thereby making it possible for clinicians to target their IIPT more precisely.